Cox Regression untuk Mengetahui Besaran Risiko Terjadinya Kekambuhan Kembali (Relaps) Penyalahgunaan Narkoba - Kardita Puspa Monitasari; Diah Indriani (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2017)
Relapse happened because of factor that affected an addict back to the previous state. Recurrence rate off an addict that had been treated on a various therapeutic center and rehabilitation was higher from 60% until 80%. Relapse occurred when an individual returned to his/her pattern of addiction or back to deviant behavior. The purpose of this research is identifying factors that can affect relapse. This research is analytic observational research using cross sectional design. The data were collected from 30 people who still undergo the rehabilitation. Data analysis of this research is using cox regression. Result of this research showed that someone who has medium level of knowledge has a risk to get relapse 41.26 times higher than someone who has a lower level of knowledge. Respondent with high level of knowledge might got relapse 1.4 times higher than respondent that has a low level of knowledge. While the variable of a medium peer environment showed risk of 3.31 times higher got a relapse than a high peer environment. Respondent that has a low peer environment might got relapse 1.45 higher than a high peer environment. In this reseach, there are two factors that can affect relapse event, those factors were the level of knowledge and peer environment. The biggest risk for an addict to get their relapse is knowledge, so that the knowledge of narcotics should be given more and also to make their peer environment support them in avoiding the narcotics.